1997
DOI: 10.1074/jbc.272.3.1628
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Skeletal Muscle Ca2+ Release Channel (Ryanodine Receptor) by Ca2+ and Monovalent Cations and Anions

Abstract: The effects of ionic composition and strength on rabbit skeletal muscle Ca 2؉ release channel (ryanodine receptor) activity were investigated in vesicle- 45

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
200
5
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(224 citation statements)
references
References 28 publications
17
200
5
2
Order By: Relevance
“…As shown previously [3], in the absence of Zn# + the binding expressed a bell-shaped dependence on [Ca# + ] f and was increased significantly by 10 mM caffeine, especially at low [Ca# + ] f ( Figure 5). …”
Section: Biphasic Time Course Of the Effect Of Zn 2 +mentioning
confidence: 53%
See 4 more Smart Citations
“…As shown previously [3], in the absence of Zn# + the binding expressed a bell-shaped dependence on [Ca# + ] f and was increased significantly by 10 mM caffeine, especially at low [Ca# + ] f ( Figure 5). …”
Section: Biphasic Time Course Of the Effect Of Zn 2 +mentioning
confidence: 53%
“…It has been shown that the function of RyR1s can be modulated by various endogenous and exogenous factors, including caffeine, Mg# + and adenine nucleotide [2][3][4][5]. It is thought that caffeine increases the apparent affinity of the activation site for Ca# + , whereas Mg# + inhibits ryanodine binding by competing with Ca# + for the Ca# + activation site [3,4].…”
Section: Interaction Of the Effects Of Zn 2 + And Other Ryr Modulatorsmentioning
confidence: 99%
See 3 more Smart Citations